Association between lifestyle-related risk behaviors, chronic diseases, and body image distortion: gender differences in follow-up 1 of the ELSA-Brasil cohort - Ana Luísa Patrão; Sheila Maria Alvim Matos; Emanuelle Goes; Conceição Nogueira; Rosane Harter Griep; Maria de Jesus Mendes da Fonseca; Liliana Rodrigues; Estela M. L. Aquino; Maria da Conceição Chagas de Almeida (Health Psychology and Behavioral Medicine)
Aim: To determine the prevalence of body image accuracy/distortion in Brazilian men and women and to investigate sociodemographic and lifestyle-related factors, and the presence of chronic diseases associated with body image distortion.Methods: Data from 6,357 men and 7,657 women participating in the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) were collected using a multidimensional questionnaire covering sociodemographic characteristics, health behaviors, heath conditions and body image perception.Results: Most participants (53.5% of the women and 54.7% of the men) were found to have an accurate self-perception of their body. When the factors associated with the perception of being heavier than reality were investigated, adopting weight loss measures and not being hypertensive proved protective against this distortion, both in women and men. Conversely, the perception of being lighter than reality was associated, in both women and men, with better education, being black or of mixed race, adopting weight loss measures and not being hypertensive or diabetic. Additional factors associated with underestimating weight were not consuming alcohol (only in women) and belonging to a lower social class (only in men).Conclusion: These findings may contribute to the implementation of public health policies and interventions to promote health and well-being in the Brazilian population.